Image guided laryngoscopy versus laryngectomy surgery: Patient safety and system review. Issue 1 (31st December 2016) - Gerlach, Thomas; Friebe, Michael H.
Abstract: Laryngectomy, open surgery on the neck, is an invasive therapeutic procedure with serious potential of constraints in everyday life, such as the loss of voice. The use of minimal invasive transoral and transnasal approaches for local treatment of laryngeal cancer could ensure better preserving of organs. Direct laryngoscopy, a widely used endoscopic procedure that requires general anesthesia is presented as well as transnasal optical fiber approaches that require only local anesthesia and would allow a deeper insertion of instruments. In this paper we present and review the different endoscopic approaches in combination with cold cutting and hyperthermal approaches for laryngeal tumor treatment with the conventional open surgery approaches. Minimal invasive surgery could provide advantages for patients and surgeons. Further improvements include robotic and other manipulation systems.